Urgensi Criminal Liability dalam Rangka Pembaharuan Punishment System Criminal of Law - Balla, Herman; Saputra, Iswandy Rani (Jurnal Litigasi Amsir, 2024)
The Criminal Code (KUHP) is not in accordance with the values prevailing in society. Guidelines in the formulation of crimes are currently only concerned with the provisions of criminal acts and mistakes without including the purpose and principles of punishment. This article aims to determine the urgency of the purpose and guidelines for criminalization to be formulated / formulated in the Criminal Code, and to analyze how the objectives and guidelines for punishment are formulated and integrated in the reform of the criminal system in the future. This article uses a normative juridical approach with a statutory and conceptual approach. The results of the study show the urgency of the objectives and guidelines for punishment due to the problems associated with the aging of the Criminal Code at this time and the development of problems that arise in the midst of public life and criminal guidelines are the basic provisions that give direction, which determine in the imposition of a criminal. instructions for judges in applying and imposing crimes. In the future the welfare and protection of the community can be realized and as a guarantor there is no decrease in the degree of humanity / dehumanization in the implementation of crimes